Dental Care in Patients under Anticoagulation Therapy: An Integrative Review - , Pedro Augusto Lopes Pinheiro; , Maria Fernanda de Oliveira; , Pâmela Luenny Forte Santos; , Tamara Brito da Silva; , Carlos Ryan Silva dos Santos; , Eliane Ferreira Sampaio; , Alinne Patierry Oliveira Pacífico Feitosa (Archives of Current Research International, 2025)
Dental care for anticoagulated patients is an increasingly important area, requiring precise protocols to ensure the safety and effectiveness of procedures. In the context of oral health promotion, a thorough understanding of the risks and benefits associated with this therapy is essential to ensure safe and effective treatments. This study aimed to analyse the safe use of anticoagulants in invasive dental procedures through an integrative review. A total of 20 articles were identified, with 15 from PubMed and 5 from Scielo. Articles were searched in the Scielo and PubMed databases, published from January 2019 to June 2024, using the English descriptors "bleeding risk" AND "anticoagulant therapy" AND "dental extraction," resulting in 20 articles. After applying inclusion and exclusion criteria, 9 articles were selected. In summary, the reviewed articles provide essential information on the non-discontinuation of anticoagulant medication before invasive dental procedures, adjunctive hemostatic options for bleeding control, and differences between newer and older anticoagulants. Among healthcare professionals, there is often a discussion about whether or not to interrupt the use of oral anticoagulants before invasive dental procedures. It is also observed that there are similar opinions regarding whether or not to suspend the medication. The appropriate conduct is to maintain the use of the medication before invasive dental procedures. Regarding the choice between traditional anticoagulants and new oral anticoagulants (NOACs), some studies suggest that NOACs may be a safer option, with lower postoperative bleeding rates compared to warfarin. This evidence supports the need for individualised approaches in the dental management of patients on anticoagulant therapy, aiming to ensure safe and effective outcomes.